The necessity of lectionary preaching in Korean Presbyterian context : a practical theological research - Lee, Keonsoo (Stellenbosch : University of Stellenbosch, 2010)
Tesis (MTh (Practical Theology and Missiology))--Stellenbosch University, 2010.